2017
DOI: 10.1007/s40544-017-0148-8
|View full text |Cite
|
Sign up to set email alerts
|

Tribology behavior on scratch tests: Effects of yield strength

Abstract: A three-dimensional (3D) scratch model is proposed to investigate the effects of yield strength of both coatings and substrates. With the help of combined Coulomb and plastic friction, the obtained results comprehensively interpret the experimental phenomena in most metals that with the growth of hardness after heat treatment the scratch friction coefficient (SFC) increases. This interpretation could not be done before. Scratch tests on the surface with or without the coating are discussed. Without the coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It should be noted that the material pile-up in front of the scratch tip, commonly observed during the scratch process, has yet to been considered for the proposed analytical model. It is also known that the substrate recovery is closely correlated with the material properties such as the elastic modulus, yield strength [21,23], and viscoelastic characteristic [44][45][46][47][48], as well as the possible influence of the crystallinity on these properties [49], which are inherently important for the scratch friction performance of polymeric materials. A comprehensive analytical investigation of polymer scratching should be further conducted when considering the above factors.…”
Section: Effects Of the Substrate Recovery On The Scofmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the material pile-up in front of the scratch tip, commonly observed during the scratch process, has yet to been considered for the proposed analytical model. It is also known that the substrate recovery is closely correlated with the material properties such as the elastic modulus, yield strength [21,23], and viscoelastic characteristic [44][45][46][47][48], as well as the possible influence of the crystallinity on these properties [49], which are inherently important for the scratch friction performance of polymeric materials. A comprehensive analytical investigation of polymer scratching should be further conducted when considering the above factors.…”
Section: Effects Of the Substrate Recovery On The Scofmentioning
confidence: 99%
“…Pelletier et al [16] numerically demonstrated that the interfacial friction significantly affects the real contact area between the scratch tip and polymethylmethacrylate (PMMA) substrate. Feng et al [23,24] considered the combined Coulomb and plastic friction effect to study the impact of the yield strength on the scratch friction behavior.…”
Section: Introductionmentioning
confidence: 99%